AlGaN/GaN/3C-SiC on diamond HEMTs with thick nitride layers prepared by bonding-first process. (1st April 2022) - Kagawa, Ryo; Kawamura, Keisuke; Sakaida, Yoshiki; Ouchi, Sumito; Uratani, Hiroki; Shimizu, Yasuo; Ohno, Yutaka; Nagai, Yasuyoshi; Liang, Jianbo; Shigekawa, Naoteru
Abstract: We fabricate AlGaN/GaN high electron mobility transistors (HEMTs) on diamond substrates by transferring 8  μ m heterostructures grown on 3C-SiC/Si templates and subsequently applying the conventional device process steps. No exfoliation of 3C-SiC/diamond bonding interfaces is observed during 800 °C annealing, the essential step for forming ohmic contacts on nitrides. The thermal resistance of HEMTs on diamond is 35% of that of HEMTs on Si, which is assumed to be the origin of smaller negative drain conductance in on-diamond HEMTs. The results imply that the bonding-first process is applicable for fabricating low-thermal-resistance HEMTs with thick nitride layers.